The behaviour of tourism market participants in the context of the development of ecotourism - Barwicka, Katarzyna; Olearnik, Janusz (Zachowania uczestników rynku turystycznego w kontekście rozwoju ekoturystyki, 2019)
This article considers the influence of ecotourism, a fast-developing form of tourism, on an important area in the functioning of the tourism market, which is the behaviour of its participants. The aim of the article is to present the way in which the developing concept and principles of ecotourism can affect the behaviour of consumers (tourists) and the activity of tour operators (providers of tourism services). The authors propose a unique research approach which consist in addressing both the expectations on the part of tourists as well as those related to business targets of the tourism industry. This article presents conceptual framework and outlines methodical approach which can be useful for the future research. Twelve types of behaviour regarding both tourists and tour operators were distinguished, followed by a description of the character of the possible influence of ecotourism on each of them. In this way the article also presents an outline of a new approach to managing business (including market relations), taking into consideration the growing popularity and importance of ecotourism
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 2, s. 18-25
Keywords: tourism; ecotourism; tourism industry; tourism market; consumer behaviour; turystyka; ekoturystyka; przemysł turystyczny; rynek turystyczny; zachowania konsumentów